Impact of Huanglongbing Pathogen Infection on the Amino Acid Composition in Both Citrus Plants and the Asian Citrus Psyllid - Zhang, Li-He; Ren, Su-Li; Su, Zheng-Qin; Xu, Pei-Ping; Ou, Da; Wang, Li-Jun; Sang, Wen; Qiu, Bao-Li (Frontiers in Physiology, 2021)
The Asian citrus psyllid (ACP) Diaphorina citri is the main vector of the pathogen Candidatus Liberibacter asiaticus (CLas), the causal agents of citrus Huanglongbing disease. Feeding by both ACP nymphs and adults on host plants allows them to obtain nutrition. Therefore, the nutritional content within the plant phloem is of much importance for their development and reproduction. The infection by pathogenic microbiomes may affect the amino acid contents of their host plants, then indirectly affect the biology of sap feeding insects. Here, we investigated the amino acid contents and their proportions in both CLas infected and CLas free citrus plants, ACP adults and also in honeydew produced by ACP nymphs. Results showed that infection by CLas had large impact on the amino acid species and proportion in all the tested target plants, ACP adults and in the honeydew of ACP nymphs. The content of total amino acids in CLas infected citrus was much higher than that of CLas free citrus. However, CLas infection significantly reduced the proportion of essential amino acids (EAAs) in these plants. When feeding on CLas infected citrus plants, ACP adults absorbed less total amino acids than those adults feeding on healthy plants, but the proportion of EAAs was significantly higher when they fed on CLas infected citrus plants. The proportion of EAAs also significantly increased in the honeydew secreted by ACP nymphs that fed on CLas infected citrus plants. However, EAA detection in the honeydew of ACP nymphs indicated that the utilization rate of EAAs by CLas positive ACP nymphs was reduced. Our study has revealed that CLas infection significantly affects the contents, proportion and utilizations efficiency of different amino acids in citrus plants, ACP adults and nymphs, leading to a developmental pattern of ACP that is more conducive to CLas transmission.